Regional headquarters of MNCs in the service industry in Singapore - Ramani Prabhu R Kalamohan (2008)
The purpose of this study is to perform an in-depth case analysis on Multi-National Corporations (MNCs) from the service sector which have set up Regional Headquarters (RHQs) in Singapore.